2017
DOI: 10.1037/amp0000066
|View full text |Cite
|
Sign up to set email alerts
|

Close relationships and the management of chronic illness: Associations and interventions.

Abstract: Self-management of a chronic illness involves not only monitoring symptoms, adhering to medication regimens, and keeping medical appointments but also making and maintaining difficult lifestyle changes. This article highlights correlational and intervention research suggesting family members are influential in children’s and adults’ illness management. The argument is made that a dyadic approach to chronic illness management that targets the influence of close relationships may yield more sustainable effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(108 citation statements)
references
References 86 publications
2
103
0
3
Order By: Relevance
“…Our research supports efforts to target older couples to collaborate in cognitive training and therapy to enhance well-being. 35 Although studies examining the efficacy of couples treatment of depression 36 and cognitive decline 37 are limited, there is growing interest in dyadic interventions for persons with dementia and mild cognitive impairment and their spousal caregivers. 38 For example, Stahl et al 39 demonstrated in a recent case study that training a spouse to be a problem-solving therapy coach can have psychological benefits not only for the person with mild cognitive impairment but also for the spouse.…”
Section: Resultsmentioning
confidence: 99%
“…Our research supports efforts to target older couples to collaborate in cognitive training and therapy to enhance well-being. 35 Although studies examining the efficacy of couples treatment of depression 36 and cognitive decline 37 are limited, there is growing interest in dyadic interventions for persons with dementia and mild cognitive impairment and their spousal caregivers. 38 For example, Stahl et al 39 demonstrated in a recent case study that training a spouse to be a problem-solving therapy coach can have psychological benefits not only for the person with mild cognitive impairment but also for the spouse.…”
Section: Resultsmentioning
confidence: 99%
“…More children are surviving and living with chronic illnesses (CIs; Compas, Jaser, Dunn, & Rodriguez, ). Approximately 15–19% of the children in the United States face CIs (Churchill, Villareale, Monaghan, Sharp, & Kieckhefer, ; Martire & Helgeson, ; U.S. Department of Health and Human Services, ). A CI is a physical or mental condition that requires frequent medical care and hospitalizations, does not remit spontaneously, may last for a long period of time, may not be cured, and prevents involvement in regular activities, such as attending school (Compas et al, ; Ollendick & Schroeder, ; Trowbridge & Mische‐Lawson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of couple-oriented interventions for the management of chronic illnesses has been established (Martire & Helgeson, 2017;Martire, Schulz, Helgeson, Small, & Saghafi, 2010), and the current work uncovered aspects of communication that may be important for such interventions. A recent meta-analysis has suggested the small, yet stable, effect that marital quality has on health (Robles, Slatcher, Trombello, & McGinn, 2014).…”
Section: Discussionmentioning
confidence: 99%